An evaluation of the effectiveness of 'comic strip conversations' for addressing the target social behaviours of primary-aged pupils on the autistic spectrum - Page, Joanne (2016)
Educational provision for children with autism is increasingly being made within mainstream settings and a range of intervention strategies to cater for the diverse needs of this heterogeneous population are needed (Ali & Frederickson, 2006). This research presents an evaluation of ‘Comic Strip Conversations’ (CSCs) (Gray, 1994b) for addressing the target social behaviours of five primary-aged pupils with autism in mainstream schools. CSCs are a story-based intervention which use visual systems designed to support understanding of situations and encourage more appropriate social behaviours in individuals with autism. A systematic review of existing research into the effectiveness of CSCs highlights the limited evidence base that currently exists. A series of multiple-baseline across behaviours single-case experimental designs (SCEDs) were implemented for four participants, in which two specific behaviours were targeted through a CSC intervention. An A-B SCED was implemented for a fifth participant, targeting a single behaviour. Repeated measures were taken through structured observations to assess the frequency of target behaviours. These measures were triangulated with pre- and post- measures of staff perceptions of the target behaviours and intervention effectiveness. This research additionally explored the relative impacts on behaviours of creating single versus multiple CSCs. The repeated measures data was analysed using a combination of visual analysis and effect size analysis (Tau-U). The outcomes of this indicated mixed results, with the intervention appearing to be moderately to highly effective in addressing at least one target behaviour for three of the five participants. Outcomes in terms of changes in staff perceptions of target behaviours and ratings of intervention effectiveness were similarly mixed and did not consistently triangulate with the repeated measures data. The behaviour targeted through multiple CSCs demonstrated greater improvement than the behaviour targeted through a single CSC in three out of four participants, however the difference was negligible in one case. Therefore, no clear association between intervention frequency and outcome could be concluded. The results are considered in view of the limitations of the research, taking into account the research design, characteristics of the data obtained, and threats to internal validity. Implications for practice are outlined and suggestions are made for future research. The research concludes with some support for CSCs as a promising intervention which may aid the development of socially appropriate behaviours for some pupils with autism.